Safety and efficacy of an injectable nerve‐specific hydrogel in a rodent crush injury model. Issue 2 (25th November 2021) - Prest, Travis A.; Meder, Tyler J.; Skillen, Clint D.; Marchal, Lucile; Soletti, Lorenzo; Gardner, Paul A.; Cheetham, Jonathan; Brown, Bryan N.
Abstract: Introduction/Aims: While the peripheral nervous system has the inherent ability to recover following injury, results are often unsatisfactory, resulting in permanent functional deficits and disability. Therefore, methods that enhance regeneration are of significant interest. The present study investigates an injectable nerve‐tissue‐specific hydrogel as a biomaterial for nerve regeneration in a rat nerve crush model. Methods: Nerve‐specific hydrogels were injected into the subepineurial space in both uninjured and crushed sciatic nerves of rats to assess safety and efficacy, respectively. The animals were followed longitudinally for 12 wk using sciatic functional index and kinematic measures. At 12 wk, electrophysiologic examination was also performed, followed by nerve and muscle histologic assessment. Results: When the hydrogel was injected into an uninjured nerve, no differences in sciatic functional index, kinematic function, or axon counts were observed. A slight reduction in muscle fiber diameter was observed in the hydrogel‐injected animals, but overall muscle area and kinematic function were not affected. Hydrogel injection following nerve crush injury resulted in multiple modest improvements in sciatic functional index and kinematic function with an earlier return to normal function observed in the hydrogel treated animals as compared to untreated controls. While no improvements in supramaximal compound motor action potential were observed in hydrogel treated animals, increased axon counts were observed on histologic assessment. Discussion: These improvements in functional and histologic outcomes in a rapidly and fully recovering model suggest that injection of a nerve‐specific hydrogel is safe and has the potential to improve outcomes following nerve injury.